(untitled) - FITRIADI, ANGGAH (Language Horizon: Journal of Language Studies, 2016)
Abstrak Salah satudialekdariBahasaInggrisadalahdialek orang Afrika-Amerika.Dialekinidigunakanoleh orang-orang keturunanAfrika-Amerika. Definisidialeksendiriadalahbahasa yang belum di standarisasidanjugatidakmemiliki status resmi. BahasadialekinggrisAfrika-Amerikamemilikibeberapanamaatausebutanantara lain: Negro dialect, Nonstandard Negro English, Negro English, American Negro Speech, Black Communication, Black Dialect, Black Folk Speech, Black Street Speech, Black English, Black English Vernacular, Black Vernacular English, Afro American English, African American English (AAE), and African American Language. bahasadialekiniberbedadenganStandartBahasaInggrisAmerikadalamfonologi, tatabahasadankosakatanya. Dalampenelitianini, penelitibertujuanuntukmendeskripsikanpenggunaan AAVE olehpelayanwanitakulithitam di Amerikatepatnya di Jakson, Mississippi. diskripsinyameliputidari (1) apasajafiturdari AAVE yang digunakanolehpelayanwanita di film The Help; (2) bagaimanapenggunaanfiturdari AAVE olehpelayanwanita di film The Help dan (3) bagaimanadampakpenggunaanfiturdari AAVE dalamjalanceritadalam film The Help. Penelitianinimenggunakanmetodedeskriptifkualitatifdenganmenggunakanteorifitur AAVE karya Lisa J. Green (2002).Pengumpulan data dilakukandengancaramendokumentasiucapan-ucapan yang dilontarkanolehempatpelayanwanita di film “The Help”. Dokumentasi data dilakukanmelaluibeberapa proses yaknimelihat film, mendengarkan dialog, menulis data, mengelompokkan data, pemberiancatatankhusus, danpengecekkan data ulanglalu data yang sudahterkumpulakandianalisamelaluitahappemahaman dialog, analisadanpengelompokkan data berdasarkanfiturnyadanmenjelaskan alas an daripenemuantersebut. Berdasarkandarihasilanalisis, penelitimenemukanbeberapafiturdari AAVE yang dilakukanolehpelayanwanitadalam film The Help. Fitur AAVE dalamfonologi yang ditemukanpada data antara lain pergantianing/in, pergantian ask/aks, penghapusanbunyi /r/ dan /l/, pengurangankonsonanakhirtunggal, penguranganakhirkonsonandalamkluster, monoftong, perubahanbunyi /th/ menjadi /d/ atau /t/, pengurangansuku kata pertama, sedangkanfitur AAVE dalamtatabahasa yang ditemukandalamtutur kata pelayanwanitaantara lain tidakadanya kata kerjapenghubung, tidakadanya kata kerja bantu, peraturansubjek-kata kerjatidakberlaku, tidakmengubahkebentuk possessive, tidakmengubah kata kerjabentuk kata kerjauntuk orang ketigatunggal, inversi kata kerjadan verb di kalimattanyadankompletif done. Namun, hanyaditemukanduakategoridarifitur AAVE dalamkosa kata yang dilakukanolehpelayanwanitaantara lain penandalisan be danlogat. Fitur-fiturtersebutdiatasdigunakanolehparapelayanwanitauntukberkomunikasidenganlawanbicarabaikkepada orang kulitputihdanjuga orang kulithitam. Usia, etnisitasatauras, dan status social hamper samasekalitidakmempengaruhimerekadalammenggunakanfitur AAVE di setiaptutur kata mereka. Tetapi, penelitianinimenemukanbahwasanyapendidikandapatmempengaruhidalampenggunaanbahasakhususnya SAE dan AAVE yang digunakanolehpembicara. Secarasingkat, ucapan0ucapan yang dilontarkanolehkarakterpelayanwanita di dalam film “The Help” hampirsemuanyamengikutiaturan-aturan AAVE dibandingkan SAE. Bagaimanapunjuga, halinitidakberartibahwapelayanwanita di film inihanyamenggunakan AAVE dalampercakapansehari-harimereka. Dalambeberapakasus yang di temukandalam study inimenunjukkanbahwapelayanwanitaterkadangmenggunakanBahasaInggris yang sudah di standartkanketikaberkomunikasidengan yang lain khususnyadengan orang-orang kulitputih. Kata Kunci: bahasaInggris, AAVE, keturunanAfrika-Amerika, Film Abstract African American Vernacular English is a vernacular English spoken by African Americans. Vernacular itself refers to a language which has not been standardised and which doesn not have anofficial status. African American Vernacular English has other names or terms. Those terms are negro dialect, Nonstandard Negro English, Negro English, American Negro Speech, Black Communication, Black Dialect, Black Folk Speech, Black Street Speech, Black English, Black English Vernacular, Black Vernacular English, Afro American English, African American English (AAE), and African American Language. This vernacular is different from SAE (Standard American English) in its phonology, grammar and lexical. In his study, the researcher aimed to describe the use of AAVE in Blacks’ utterances in the movie “The Help”. “The Help” is a movie which tells about the life of Blacks in America specifically Jackson, Mississippi. The description consists of (1) what AAVE features used by maids in the movie The Help; and (2) how the maids apply the features of AAVE in the movie The Help. The study used descriptive qualitative method using the AAVE features theory conducted by Lisa J. Green (2002). The data is collected by documenting the utterances of the 4 maids in the movie “The Help” through several processes include watching the movie, listening the dialogue, transcribing the data, classifying the data, note taking, and cross-checking the data and then the collected data is analyzed through the process of understanding the dialogue, Analyzing, classifying and calculating the data based on its class and explaining the reason of the finding. The results shows that this study has found some AAVE features used by maids in the movie. AAVE features in Phonology, they are ing/in alternation, ask/aks alternation, /r/ and /l/ deletion, single final consonant reduction, final consonant reduction in cluster, monophthong, initial /th/ changing as /d/ or /t/, reduction of first syllable. While the AAVE features in Grammar which found in the data are absence of copula, absence of auxiliary verb, subject-verb non-agreement, unmarked third person singular verb, existential dem, multiple negation, the use of ain’t, unmarked possessive, inversion of subject-verb in question and completive done. However, there are only two categories of AAVE features in lexical used by maids. They are verbal marker be and Slang. Those features are used by maids to communicate towards both Whites and Blacks. Age levels, Ethnicity and social status almost does not have a role in the application of the features in maids’ utterances. However, this study finds that education effects on the way language specifically SAE and AAVE used by the speaker. In brief, the utterances of maids characters in the movie “The Help” are mostly follows the rule of AAVE instead SAE. However, it does not mean that maids only use AAVE in their daily activity. In some cases show that maids sometimes use standardized English when communicates with others specifically toward whites. Keywords:English, AAVE, African-Americans, Movie